Climate-related credit risk: Rethinking the credit risk framework - Redondo García, María Elena; Aracil Fernández, Elisa María (My University, 2024)
Climate change poses a significant financial risk to economic agents, as well as a potential systemic risk threat due to uncertainty and non-linearity of the transition risks to a zero-carbon economy. This article conducts a literature review to examine how climate-related risks (CRR), both physical and transition, can be integrated into banks’ credit risk assessment and monitoring processes . We find four thematic areas in the literature: CRR dynamics, CRR toolkit, CRR intelligence, and CRR pricing. A framework emerges from the review, that rethinks credit risk assessment and monitoring setting to incorporate climate risks. We find that extant literature on integrating CRR into banks' credit risk assessment and monitoring is in its early stages, with CRR tools and methodologies under construction. We also find that uncertainty, non-linearity, geographic and industrial dependency, and non-reversibility difficult the assessment of CRR financial impacts. Moreover, CRR data presents comparability, availability, and reliability issues. Finally, evidence reveals that current financial prices do not fully reflect CRR. We suggest a set of future lines of research in the four thematic areas to address these challenges. Our findings provide important implications to policymakers regarding ex-ante assessment of the short- and long-term financial impacts of the forthcoming environmental transition policies and regulations and the potential for prudential regulatory action. Our framework may assist bank managers in CRR integration into credit risk, and their understanding of the constraints and complexities in this effort. The findings open avenues for future research on the role of financial institutions to foster the energy transition.